Event-triggered adaptive neural tracking control for MSVs under input saturation: An appoint-time approach. (1st June 2022) - Liu, Gang; Du, Bin; Lin, Bin; Zhang, Weidong
Abstract: This paper addresses an event-triggered tracking control issue for marine surface vessels (MSVs), which suffers from uncertain dynamics, unknown external disturbances and input saturation. To facilitate the implementation of backstepping design procedure, the input saturation nonlinearity is replaced by a smooth Gaussian error function. Under the backstepping design framework, introducing a nonlinear transformation and integrating the indirect adaptive neural, single parameter learning and event-triggered control techniques, a novel event-triggered neuroadaptive appoint-time tracking control scheme is proposed. Compared with most existing results, the proposed control solution is of the following notable characteristics: (1) the convergence time and accuracy of the position and velocity errors are determined by designer offline; (2) only one unknown parameter needs to be updated, which reduces the computational burden of control system greatly; (3) it decreases mechanical wear of the MSV actuators by reducing the response frequency of actuators to the control command. The theoretical analyses validate that all signals of the closed-loop trajectory tracking control system are bounded. Simulation results illustrate the effectiveness of the developed scheme. Highlights: The proposed control scheme guarantees that the position and velocity errors converge to a predefined neighborhood of origin in an appoint time, which can be determined off-line by user. Only one unknown parameter needs to be updated in this work, which can reduce the computational burden greatly. This work establishes an event triggering mechanism between the control law and the actuator, which can effective reduce the unnecessary mechanical wear of actuator.